ANALISIS HAKIKAT DAN TUJUAN PENDIDIKAN ISLAM DALAM KONSEP TARBIYAH, TA’LIM, DAN TA’DIB - Akhmad Faisol; Fina Dwi Novita Sari; Sahrul Gunawan; Muhammad Qoyim; Devy Habibi Muhammad (As-Sulthan Journal of Education, 2026)
This study aims to analyze the nature and objectives of Islamic education through the development of the concepts of tarbiyah, ta’lim, and ta’dib as the main foundations of the Islamic education system. Using a qualitative method with a library research approach based on relevant books and scholarly articles, the findings reveal that tarbiyah focuses on the gradual process of nurturing and developing human potential, ta’lim emphasizes the transfer of knowledge, and ta’dib is directed toward cultivating manners, morality, and ethics in learners. These three concepts complement one another in forming a comprehensive educational system that encompasses cognitive, affective, and psychomotor domains. Furthermore, the integration of tarbiyah, ta’lim, and ta’dib has significant implications for the understanding and practice of Islamic education, including the development of learners’ potential, character building, and educational policy within institutions. Islamic education is therefore not only oriented toward mastery of knowledge, but also toward shaping individuals who are faithful, knowledgeable, and morally virtuous, making this concept a strategic foundation for realizing a balanced education between knowledge and action while remaining relevant to contemporary challenges.